Desenvolvimento e validação de método por cromatografia líquida em fase reversa para avaliação de interleucina-11 humana recombinante. Correlação com o bioensaio - Souto, Ricardo Bizogne (2011)
Interleukin 11 (IL-11) is a multifunctional cytokine in the IL-6 type family of long-chain helical cytokines, which modulates the proliferation, differentiation and maturation of various types of hematopoietic cells. Recombinant human interleukin-11 (rhIL-11) produced by DNA technology in Escherichia coli is currently being used worldwide for the prevention of thrombocytopenia and to reduce the need for platelet transfusions after myelosuppressive chemotherapy in patients with nonmyeloid malignancies. A stability-indicating reversed-phase liquid chromatography (RP-LC) method was validated for the assessment of recombinant human interleukin-11 (rhIL-11) in biopharmaceutical formulations. The RP-LC method was carried out on a Jupiter C4 column (250 mm x 4.6 mm i.d.), maintained at 25ºC. The mobile phase A consisted of 0.1% TFA and the mobile phase B was acetonitrile with 0.1% TFA, run as follows: time 0 to 0.1 min 40% of B; from 0.1 to 30 min linear up to 65% of B; from 30.01 to 31 min linear down to 40% of B, maintained up to 40 min. The flow rate was 1 mL/min, and using photodiode array (PDA) detection at 214 nm. Chromatographic separation was obtained with a retention time of 27.6 min, and was linear over the concentration range of 1 200 μg/mL (r2 = 0.9995). The limits of detection and quantitation were 0.34 and 1.12 μg/mL, respectively. Specificity was established in degradation studies, which also showed that there was no interference of the excipients. The accuracy was 100.22% with bias lower than 1.25%. Moreover, the in vitro cytotoxicity test of the degraded products showed non-significant differences (p>0.05). The proposed method was applied to the assessment of rhIL-11 and related proteins in biopharmaceutical dosage forms, and the results were correlated to those of a bioassay, showing a higher mean difference of the estimated content/potencies of 2.60% for the RP-LC method, aiming to establish new alternatives to monitor stability, improve quality control and thereby assure therapeutic efficacy of the biological medicine.